Deconstructable steel–fibre reinforced concrete deck slabs with a transverse confining system. (5th January 2016) - Moradi, M.; Valipour, H.; Foster, S.J.; Bradford, M.A.
Abstract: This paper investigates the behaviour of transversely-restrained precast steel–fibre reinforced concrete (SFRC) slabs in a demountable composite bridge deck. Fourteen precast SFRC slabs were tested under static point loading. The slabs were restrained using external demountable straps and cross-bracings to mobilise arch action and so enhance the load carrying capacity of the SFRC slabs, being partially or fully devoid of conventional reinforcing bars. The configuration and proportion of the reinforcing bars, concrete compressive strength, dosage of fibres and the type of external restraining system (cross-bracing/strap) were the main variables in the tests. It is concluded that steel fibres with 0.5% dosage can significantly increase the load carrying capacity of the externally restrained precast deck slabs devoid of steel bars and the transverse confining system (i.e. ties/straps and cross-bracings) can increase the energy-based ductility index of the SFRC deck slabs. Furthermore, it is shown that replacing part of conventional reinforcing bars with structural steel fibres can slightly improve the energy-based ductility of externally restrained SFRC/RC precast deck slabs. Graphical abstract: Highlights: A deconstructable composite bridge deck with SFRC slabs is developed Transverse confinement increases the energy-based ductility index of SFRC slabs Transverse confinement significantly increases the loading capacity of SFRC slabs Steel bars in deck slabs with transverse confinement can be replaced by steel fibres